Determinação de metais como contaminantes em formulações de eritropoetina empregando métodos voltamétricos - Garmatz, Júlia Cristina (2007)
The contamination of renal failure patients by metals can be associated to the presence of these metals in the medication, since they can be absorbed by the organism. The level of contamination caused by medication, in these cases, depends strongly on the quality of medication used in the treatment. Among the possible contaminants, there are metals such as aluminum, chromium and nickel. Therefore, the development of analytical methodologies for the quality control of medicaments used by anemic patients is of great importance. In the present work, the presence of Al, Cr and Ni as contaminants in erythropoietin formulations (EPO), a renal antianemic, was investigated by developing and optimizing an adsorptive cathodic stripping voltammetric (AdCSV) method. It involves the optimization of a pretreatment step of samples by using UV irradiation for decomposition of matrix organic components. The AdCSV method is based on the adsorptive deposition of the complex formed at the electrode surface and the subsequent reduction of ligand (or metal) during the cathodic potential scan. The results found for Al, Cr and Ni in the studied samples, after performing the pretreatment step, show the applicability of the method for the determination of Al, Cr and Ni as contaminants in this kind of samples. The developed voltammetric methods are advantageous in relation to other existing methods concerning the high sensitivity of measurement if associated to the pretreatment step by UV irradiation associated with the addition of H2O2.